Surveillance and Entanglement: How mandatory sex offender registration impacts criminalised survivors of human trafficking - Mogulescu, Kate; Goodmark, Leigh (Anti-Trafficking Review, 2020)
This short article describes how some victims of human trafficking in the sex industry in the United States are prosecuted alongside traffickers and put on sex offender registries. The result is both a criminal record and an indefinite digital mark that limits their ability to find a job, settle in a new community, and see their children. The article concludes with a call for a careful, critical look at the system of sex offender registries and, more broadly, policing and prosecution strategies, including in cases of human trafficking, in the United States.